Cinque Terre (Five Lands) in the mouth of the ouroboros - Sowa, Paweł (Turystyka – to znaczy co? Uroboros czy Feniks, 2025)
The Cinque Terre (Five Lands) is a picturesque stretch of Italy’s coastline along the Ligurian Sea with outstanding natural and cultural value which has been designated a UNESCO World Heritage Site. Due to its attractiveness, it has become a destination for numerous tourist visits and this has caused it to struggle with the phenomenon of overtourism in recent years. The aim of the article is to show the scale of this problem and its impact on the living conditions of the local community and the state of its natural environment. The towns of Cinque Terre are threatened not only by the loss of a vibrant identity, but also by unfavorable changes in the natural environment.